The biology of the Mango Leafhopper, Idioscopus nitidulus in Malaysia - Mohd Nordin, A. Razak; Ibrahim, Abdul Ghani (Universiti Putra Malaysia Press, 1995)
Field experiments were conducted to study the biology of the mango leafhopper, Idioscopus nitidulus Walk., following outbreaks in north Peninsular Malaysia in 1986 and 1987. The developmental period on inflorescense was 13.77±0.25 days for males and 13.50±0.60 days for females, and mean incubation period of eggs was 3.85±2.00 days. Hoppers reared on the inflorescence produced 277±110 eggs with a hatchability rate of 90.2±8.4%; those on shoots produced 149±57 eggs and had a hatchability rate of54.8±22.0%. A female mating only once laid 176±72 eggs, whereas multiple mated females produced 149±57 eggs. On shoots in the field, the longevity of females (69.8±9.8 days) was not significantly different from that of males (60.5±8.5 days).